On tidal array layout sensitivity to regional hydrodynamics representation - Connor Jordan; Daniel Coles; Fraser Johnson; Athanasios Angeloudis (International Marine Energy Journal)
Hydrodynamic models are required to predict the power produced by a tidal array and the impact on the surrounding environment. The influence of common model inputs to layout optimisation are investigated herein. This is achieved using a shallow water equation based tidal array modelling framework, Thetis, coupled with a low cost analytical wake model (FLORIS) that allows for rapid assessment of the impact of small changes in hydrodynamic results on array micro-siting. The sensitivity of array optimisation at an intermediate development point (43 turbines) is interrogated through both artificial flow field manipulation and variation of inputs pertinent to optimisation. A small margin exists in which an optimised layout performs efficiently for a deviation in flow prediction accuracy. However, incorrect flow predictions by a range sensitive to model inputs led to a ≈5% variation in array efficiency relative to a control case. The sensitivity of flow field variance on energy yield and layout are substantial. Comparing arrays sited using different bathymetry resolution models leads to a discrepancy on average of almost 2% to average array power. Arrays sited for different mesh resolution and friction representation also changes exceeding 0.85%. For array developers and the future of this nascent industry, acquisition of reliable bathymetry data coupled with repeated calibration of array models is critical for accurate array power and efficiency.